Virginity : some master myths. A study of Biblical and other ancient references to virginity in the context of HIV / AIDS in South Africa - Bruce, Patricia (Neotestamentica, 2004)
Cultures that value virginity often seek to control women closely. This paper examines ancient Jewish, Greek and early Christian attitudes to virginity, setting them in dialogue with contemporary cultural initiatives in KwaZulu-Natal that aim to promote virginity as part of the fight against HIV / AIDS. The Church, which has traditionally advocated virginity, needs to exercise caution in such a situation, where its own traditions and teachings might combine with cultural practices to entrench patriarchy. Discussion of the topic of virginity / sexual abstinence in 1 Corinthians 7, leads to the conclusion that Paul's views (when considered in his own context) were moderate and not aimed at restricting the freedom of women. Subsequent interpretations of Paul's views have, however, been oppressive to women.
Free